DETERMINAN PENGUNGKAPAN CSR DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Yulia Yunita Yusuf (University of Merdeka Malang, 2017)
The purpose of this study to test whether the slack resources, the company's financial leverage, firm size, and board size can be said as the determinant of the disclosure of Corporate Social Responsibility (CSR), and its influence on the value of the company. Results of a study of manufacturing companies indicates that slack resources, firm size, and board size affect the disclosure of CSR that are detrimental to the disclosure of CSR, and the company's financial leverage does not affect the disclosure of CSR. The test results also show that the direct effect of slack resources, the company's financial leverage, firm size, board size, and disclosure of CSR affect the value of the company. Results of testing analysis does not directly support the indirect effect of slack resources, company size, and the board size to corporate value through CSR, but the CSR was not able to mediate the effect of leverage on firm value. The results of this study support the stakeholder theory, slack resource theory, and good corporate governance theory DOI : https://doi.org/10.26905/jbm.v4i2.1701